BIOGRAFI DJUNIR 1945-1950 SEORANG PEJUANG MEMPERTAHANKAN KEMERDEKAAN DARI KAMBANG PESISIR SELATAN - Dasman, Silvi Seplin; Jarudin, Jarudin; Kaksim, Kaksim (Pendidikan Sejarah, 2013)
This writing is a study of thematic biography that describes the Djunirâs struggle at any time. Djunirâ struggle as a patriot who deserves to be traced, because it related with history and played a role as a fighter. The problem studied is how the life story of Djunir before he entered to military members and how Djunirâs struggle in defend the liberty from the republic of Indonesia in Kambang. The method used in this research is the historical method is done by several stages. The first stage is heuristic, heuristic is to collect relevant data either studies library or interview. Studies library, the writer obtained posts from history books or scientific papers while interviews conducted with some figures who know about Djunirâs struggle. The second stage is criticism source; criticism source is to do the data testing through internal and external criticism. The third stage is data interpretation. The fourth stage is historiography; historiography is the presentation of data in scientific papers thesis.The result of research showed that Djunir born from educated family and shoulders the traditional values and religions that exist in his region. Djunir study in the school that was founded by the Dutch, that called as school of the populace (SR). Since Indonesia was independent, the Dutch re-colonize Indonesia and also Kambang in south coast. From the result of research above, so we can conclude that djunir has a character to be member of BKR (People Security Agency) which is chaired by Lettu Sae Ahmad. Then follow to investigate the Dutch in several region such as, Koto Pulai area, Medan Baik and Kayu Gadang. Furthermore, Djunir believed by Lettu Sae Ahmad to be chairman of group to gather his friends to wage war in Marapalam area to drive out the Dutch Army.